ANALISIS WACANA BODY SHAMING DALAM FILM IMPERFECT (STUDI ANALISIS WACANA TEUN A. VAN DIJK) - Nugraha, Putri Larasati; Amanda Gelgel, Ni Made Ras; Alit Suryawati, I Gusti Agung (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2021)
Imperfect film features body shaming as the main focus of the story as well as depicting the impact felt by victims due to continuous body shaming. This research was conducted to find out the discourse displayed by Ernest Prakasa as director in the film "Imperfect". This qualitative research uses the method of analysis of the discourse model of Teun A. Van Dijk. The results of this study show that the presence of standards or parameters of beauty is what influences the mindset and way of view of society until finally assessed and embraced as a value of truth and concrete." Imperfect" gives rise to several discourses, namely "criticizing one's own appearance through judgment or comparison with others", "criticizing the appearance of others in front of them", and "criticizing the appearance of others without their knowledge". Keywords: Film, Body Shaming, Discourse Analysis